2015
DOI: 10.1016/j.jfoodeng.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds, sensory quality and ice morphology in falling-film and block freeze concentration of coffee extract

Abstract: Please cite this article as: Moreno, F.L., Quintanilla-Carvajal, M.X., Sotelo, L.I., Osorio, C., Raventós, M., Hernández, E., Ruiz, Y., Volatile compounds, sensory quality and ice morphology in falling-film and block freeze concentration of coffee extract, Journal of Food Engineering (2015), doi: http://dx.doi.org/10.1016/j.jfoodeng. 2015.05.018 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 50 publications
(47 reference statements)
4
36
1
Order By: Relevance
“…For progressive FC (PFC), the studies showed higher retention of solutes in the ice fraction when it was compared with BFC. Specifically, Moreno et al compared PFC and BFC and obtained a concentrate coffee extract with final CI values close to 1.33 and 1.55, respectively. The lower CI value in PFC indicated that the ice fraction presented more solutes entrainment in the ice fraction than BFC.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For progressive FC (PFC), the studies showed higher retention of solutes in the ice fraction when it was compared with BFC. Specifically, Moreno et al compared PFC and BFC and obtained a concentrate coffee extract with final CI values close to 1.33 and 1.55, respectively. The lower CI value in PFC indicated that the ice fraction presented more solutes entrainment in the ice fraction than BFC.…”
Section: Resultssupporting
confidence: 87%
“…Hence, FC can be used as a concentration technology to protect and retain various heat‐labile components, resulting in a minimal loss of important components, as mentioned recently by Petzold et al . Thus, studies demonstrated that FC technology allows the retention of different properties in black currant juice , coffee extract and pear juice , coffee extract , and apple juice , among other liquid samples.…”
Section: Introductionmentioning
confidence: 97%
“…The total soluble solids content of the solution was monitored every 30 min using an Atago refractometer (PAL‐BX/RI, Atago, Japan). °Brix measured in the samples were converted to a percentage of total solids using the equation: %Solids = 0.87% × °Brix, as reported by (Moreno, Quintanilla‐Carvajal, et al, ; Moreno, Raventós, et al, ). Each step was completed when the concentration index (CI) reached a range of 1.4–1.5.…”
Section: Methodsmentioning
confidence: 99%
“…In the food industry, the nutritional and sensory properties of the product may be affected by the processing of raw materials at high temperatures, as is the case for concentration by evaporation. Thus, freeze concentration (FC) has been implemented as an alternative in the food industry (Moreno, Quintanilla‐Carvajal, et al, ; Moreno, Raventós, et al, ; Sánchez, Ruiz, Auleda, Hernandez, & Raventos, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore considered a mild concentration technique. [2,3] During freeze concentration water is frozen as ice crystals, which excludes the solute molecules, when the degree of supercooling is not too high. [4] Supercooling is the process of lowering the temperature below the freezing point while the ice crystals are not yet formed due to absence of nucleation.…”
Section: Introductionmentioning
confidence: 99%